Impact of Using Online Learning Platforms on Student Engagement - Banat, Azizatul; Wahyuni, Erna; Erwin, Erwin; Siti Aisyah Hanim, Siti Aisyah; Mudinillah, Adam (Journal Emerging Technologies in Education, 2024)
Background. The use of platforms in learning will affect student engagement. Online platforms are changing the traditional approach to education. This will have a significant impact on student engagement. The online learning platform as a whole can have a positive impact on students. Student engagement in learning will provide effectiveness and independence. Purpose. This research aims to identify how much impact the online learning platform has on student engagement. In addition, it can also analyze the positive and negative impacts of using online learning platforms during learning. Method. The method used in this research is quantitative method. Data collection was done by distributing questionnaires to students and teachers. The questionnaire contains statements related to the impact of using online learning platforms on student engagement. This statement is loaded into google from which the results will be processed through the SPSS application. The data obtained can be tested by proving the statements listed on Google from. This is adjusted to the facts that often appear in the world of education. Results. The result of this research is that the impact of online platform on student engagement can be effective. Technology developed in online learning will have the potential to increase student engagement during learning. But on the other hand, it still considers the factors that will affect the maximization of the benefits of the online learning platform. Conclusion This research can be concluded that the use of platform in online learning will affect the engagement of students. Maximum use of the platform will be able to provide technological accessibility as well as adequate training for educators and students. The utilization of online platform will increase the effectiveness of distance learning. It will allow flexibility and ease of interaction between students.